SOCIAL SIGNIFICANCE OF COLOR - Verma, Rashmi (International Journal of Research -GRANTHAALAYAH, 2014)
India has always been exalted and remembered fondly as country of symbolic colors. To an outsider, its colorful culture, streets, and stories seem like a page out of an ancient folk tale. But color, in essence, has been a large part of the Indian consciousness. From the deep orange marigold flowers that bejewel almost every celebration to the deep hues of red that deck up the bride on her most important day, colour of India has, over time, become synonymous with religion- an expression of faith and beliefs. In a country where a deep understanding of prevalent diversity is perhaps the only common thread that ties its people together, India is a magical experience that ought not to be missed.in a country as diverse and culturally vibrant as India, it is perhaps the common, lifestyles, and tradition. The symbolism of color stand out and control every aspects of life in India , be it religion, politics, festivals, or celebration .in India, be it north , south, west, or east, color and culture go hand in hand . Just like many other culture across the world, there are some typical classification of color to be found in India.